2021
DOI: 10.1186/s12886-021-02198-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of depth perception and association of severity in Glaucoma patients and suspects

Abstract: Background To evaluate depth perception in Primary open angle glaucoma (POAG), glaucoma suspects compared to controls and to determine the association between depth perception and severity of glaucoma. Methods This was a hospital based, comparative, cross-sectional study. The ethical clearance was taken from institutional review committee of Institute of Medicine [Reference no.399 (6–11) E2 077-078]. Agematched, equal number of participants in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The same visual stimuli and task procedures were also used to test patients with strabismus, and increased error-in-depth values for 3D-SfS were associated with a lack of binocular stereopsis [ 16 ]. Therefore, the larger thresholds observed for 3D-SfS in this study could be attributed to impaired binocular depth perception, which is also observed in glaucoma [ 8 , 9 ]. However, compared with the strabismus patients, those with glaucoma were less able to distinguish the brightness of luminance.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The same visual stimuli and task procedures were also used to test patients with strabismus, and increased error-in-depth values for 3D-SfS were associated with a lack of binocular stereopsis [ 16 ]. Therefore, the larger thresholds observed for 3D-SfS in this study could be attributed to impaired binocular depth perception, which is also observed in glaucoma [ 8 , 9 ]. However, compared with the strabismus patients, those with glaucoma were less able to distinguish the brightness of luminance.…”
Section: Discussionmentioning
confidence: 56%
“…The binocular depth perception of individuals with confirmed or suspected glaucoma is impaired due to disruption of binocular interactions [ 8 , 9 ]. Depth structure is impaired but can still be perceived; pictorial monocular depth cues, such as shading and texture, and monocular motion parallax cues contribute to this capability [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%